“Implementación de un banco de pruebas de ensayos no destructivos para la carrera de electromecánica de la Universidad Técnica de Cotopaxi extensión La Maná”. - Quintana Romero, Pablo Paul (2023)
This research project is based on a study of a non-destructive testing test bench in the laboratory belonging to the La Maná Extension Technical University of Cotopaxi. Non-destructive testing (NDT) are non-invasive techniques to determine the integrity of a material, component or structure or to quantitatively measure characteristics of an object. These tests do not affect the properties, dimensions and use of the tested parts. Non-destructive testing methods are used in the industry to assess the integrity and properties of materials or components without damaging the object under investigation. Destructive testing of materials is used to verify that the properties of materials meet these design specifications, which in turn are often determined by standards and regulatory bodies. Through the implementation of this technique, the non-destructive testing test bench, the students of the electromechanical career will acquire new learning and carry out their respective practices to benefit in a real and practical way in carrying out non-destructive inspections and observe the facilities that the equipment offers for the detection of volumetric discontinuities of the piece to be inspected, which is important in the application of non-destructive tests for a good quality control in the industry in general.